SECOND LANGUAGE LEARNING IN THE CLASSROOM - Nurmukhamedova Iroda Aynabekovna (World Scientific Research Journal, 2025)
Abstract: Effective second language learning in classrooms requires a balanced approach that integrates both meaning and form. This paper explores key influential proposals for effective second language instruction in classroom environments and discusses the theoretical background of each approach, practical classroom implications, and how they contribute to the overall process of second language acquisition (SLA). Drawing from research in second language acquisition (SLA), the article emphasizes the importance of integrating meaning-focused and form-focused strategies and it also addresses the challenges teachers face in adopting flexible, research-based instructional practices and offers recommendations for balancing these methods to support language development across proficiency levels.